A Self –Destructing Secure Messaging System Using Multi Key Management Scheme - Amrapali Holkar; Pallavi Powar; Pooja Mhaske; Shiveta Tak (International Journal of Innovations in Engineering Research and Technology, 2021)
We propose the Pandora Messaging, an enhanced secure instant messaging architecture which is equipped with a self-message-destructing feature for sensitive personal information applications in a mobile environment along with Multi Key Security Management using Shamirs algorithm. The proposed system will be beneficial for Government officers for communicating very sensitive and confidential messages